Multi‐optical carrier generation using a microring resonator to enhance the number of serviceable channels in radio over free space optic. Issue 8 (August 2017) - Amiri, I. S.; Alavi, S. E.; Punthawanunt, S.; Yupapin, P.; Youplao, P.
Abstract: A system of radio over free space optic (RoFSO) system using the multi‐optical carriers has been generated by the microring resonators integrating an add/drop filter. These obtained carriers have shown sufficiently stable for propagating in free space channels while experiencing very low dispersion. Moreover, this technique is appropriated for higher capacity that can be serviced in a system of wavelength‐division multiplexing (WDM) RoFSO, where there are 16 carriers created, where each carrier has 12.5 GHz free spectral range (FSR) and 220 MHz full‐width at half‐maximum (FWHM) and 8 orthogonal frequency division multiplex (OFDM) signals, then they separately modulated with 8 out of these 16 carriers. After the modulation, by utilizing an free space optic (FSO) antenna, all carriers have the optical multiplexing and transmission to a FSO channel. On the receiver side, the demultiplexing is performed and finally the performance of the system subsequently is analyzed by calculation of the constellation diagram and error vector magnitude (EVM).